Formation of City Regions from Bottom-up Initiatives: Investigating Coalitional Developmentalism in the Pearl River Delta. (16th March 2023) - Zhang, Xianchun; Shen, Jianfa; Sun, Yi; Zhou, Changchang; Yang, Yu
Abstract : A conceptual framework of coalitional developmentalism is presented to advance understanding of how China's city regions have developed from bottom-up initiatives. Coalitional developmentalism extends state developmentalism with an emphasis on coalitional politics through which local state agents spontaneously form strategic coalitions to pursue regional growth. The case of the Pearl River Delta shows that a defining goal of coalitional developmentalism is to bolster regional governance capacity to overcome territorial fragmentation induced by jurisdiction-based development. First, the flexible state regulation is fundamental to developing deliberate scale-building processes toward regional governance. Second, bottom-up initiatives for building city regions emerge through a decentralized institutional structure in which governments at various scales work in an integrated fashion—via the functional integration of cities in a local official system—and the strong governance capacity of advanced cities. Third, coalitional developmentalism creates a testbed for facilitating region-based territorial growth by the central government, following long-established planning centrality paradigms. Fourth, bottom-up innovative behaviors unfold through coalitional politics associated with the top-down state spatial interventions that are a distinctive characteristic of "state spatiality" in postreform China.